An Indonesian Marine Bacterium, Pseudoalteromonas rubra, Produces Antimicrobial Prodiginine Pigments - Setiyono, Edi (ACS Omega, 2020)
[Image: see text] Red pigmented marine bacteria, Pseudoalteromonas rubra strains PS1 and SB14, were isolated from two sampling locations in different ecosystems on Alor Island, Indonesia, and cultured in the laboratory. We analyzed the 16S rRNA gene sequences and examined the pigment composition and found that both strains produced cycloprodigiosin (3), prodigiosin (4), and 2-methyl-3-hexyl-prodiginine (5) as major compounds. In addition, we detected three minor compounds: prodigiosin derivatives 2-methyl-3-propyl prodiginine (1), 2-methyl-3-butyl prodiginine (2), and 2-methyl-3-heptyl-prodiginine (6). To our knowledge, this is the first report that P. rubra synthesizes not only prodigiosin and cycloprodigiosin but also four prodigiosin derivatives that differ in the length of the alkyl chain. The antimicrobial activity of cycloprodigiosin, prodigiosin, and 2-methyl-3-hexyl-prodiginine was examined by a disk-diffusion test against Escherichia coli, Staphylococcus aureus, Salmonella typhi, and Candida albicans. We found that, at a concentration of 20 μg/mL, cycloprodigiosin showed the greatest inhibition (25.1 ± 0.55 mm) against S. aureus.